Provenance and depositional processes of extrabasinal (siliciclastic) and intrabasinal (carbonate) particles of the Tithonian–Berriasian Vaca Muerta–Quintuco System (Neuquén Basin, Argentina) (Latin American Journal of Sedimentology and Basin Analysis, 2025)
During the Early Jurassic–Early Cretaceous, between 32° and 40° S latitude, a steeply dipping active subduction zone along the western margin of Gondwana led to the development of a magmatic arc and a large back-arc depression known as the Neuquén Basin. A thick record of Tithonian–Berriasian organic rich sediments resulted from back-arc subsidence, expansion of the marine realm and flooding of the basin, which was presumably connected to the proto-Pacific Ocean through gaps in the magmatic arc. Widespread and persistent starved conditions in the basinal areas of the Neuquén Sea allowed the accumulation of a thick record of hybrid siliciclastic-carbonate sediments (“Vaca Muerta facies”), while along the eastern and southeastern cratonic basin margins, inner ramp deposits (“Quintuco facies”) were dominated by biogenic and clastic carbonates with subordinated muds, sands and salt deposits. The “Vaca Muerta Facies” is essentially composed of two (aggradational and progradational) accommodation sets. The aggradational set consists of hundred meters thick and widely distributed organic-rich silty and clayey mudstones with varying proportion of hemipelagic/pelagic siliceous and carbonate contribution, accumulated in the more distal sectors of the marine ramp under anoxic to suboxic conditions. The progradational sets, developed between the inner ramp and the deeper sectors of the basin, extend hundreds of kilometres both along and across the depositional dip, showing sigmoidal or clinoform geometries with well-defined topset, foreset, and bottomset configurations. In comparison with the aggradational sets, these intraplatform clinoforms are enriched in intrabasinal carbonate components and exhibit a reduction in organic matter content denoting a comparative increase in oxygenation of the marine bottom waters. If the productivity of pelagic biogenic carbonates was approximately constant at the basin level, the increase in the proportion of these components in the intraplatform clinoform deposits is attributed to the resuspension and dispersal of biogenic and clastic carbonate particles and grains from the internal ramp deposits ("Quintuco facies") by cross-shelf oriented barotropic currents. These currents seem to be related either to storms and/or to deflection by the Coriolis Effect (Ekman component) of highly efficient geostrophic contour currents at depths above the pycnocline. In the “Vaca Muerta facies” the supply of terrigenous siliciclastic particles has been voluminous and persistent, and the main source for these components was most probably the magmatic arc located to the western flank of the Neuquén Basin. Due to the marked stagnation and density stratification of the Neuquén Sea waters, much of the terrigenous fine-grained material was dispersed in the basinal and offshore settings of the basin by suspension plumes mobilised by baroclinic currents that travelled for long distances above the pycnocline.
Keywords: Vaca Muerta–Quintuco System; Tithonian–Berriasian; Neuquén Basin; Argentina; Fine-grained particles; Provenance; Depositional processes